1984
DOI: 10.4095/293603
|View full text |Cite
|
Sign up to set email alerts
|

Juan de Fuca Ridge atlas, SeaMARC II acoustic imagery

Abstract: This open file comprises approximately 15,000 km2 of SeaMARC II side-scan acoustic imaging data from the northern Juan de Fuca and Explorer Ridges. These data are presented in two formats: a mosaic at a scale of 1:250,000 and individual swath images (10 km x 12 km) at a scale of 1:50,000. A 20-m contour bathymetric map compiled from previously published SEABEAM datais included at a scale of 1:250,000. The individual 1:50,000 acoustic images can be easily cross-referenced to bathymetry by using the 10-m contour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Extensive hydrothermal deposits and extinct sulfide chimneys along the rift valley were discovered on previous SER mapping expeditions [ Davis et al ., ; Scott et al ., ]. Hydrothermal activity in the rift valley appears to have been locally extensive in the past.…”
Section: Geological and Petrological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive hydrothermal deposits and extinct sulfide chimneys along the rift valley were discovered on previous SER mapping expeditions [ Davis et al ., ; Scott et al ., ]. Hydrothermal activity in the rift valley appears to have been locally extensive in the past.…”
Section: Geological and Petrological Settingmentioning
confidence: 99%
“…Bathymetry of the SER summit with the distribution of the lava morphologies from SeaMARC I side‐scan sonar imagery [ Davis et al ., ; Scott et al . ] and visual observations during ROPOS dive R665 (track indicated in black, see Figure ).…”
Section: Lava Morphology and Relation With Tectonic Structuresmentioning
confidence: 99%
“…The valley floor slopes gently down toward the base of an up to 250-m-high normal-fault scarp that forms the eastern boundary of the valley. This fault cuts an extensive volcanic surface that appears to be of relatively uniform age in both 12-and 30-kHz acoustic imagery (Davis et al, 1984;Fig. 2C).…”
Section: Endeavour Valleymentioning
confidence: 99%
“…In this paper we present compilations of SeaBeam bathymetry, SeaMARC II and I acoustic imagery, seismic reflection profiles, and detailed heat flow measurements collected during a series of cruises to the southern part of Middle Valley from 1983 to 1989, and discuss the implications of these data regarding the nature of hydrothermal circulation and discharge in this sedimented rift. Some of the regional data have been published previously (e.g., Karsten et al, 1986;Davis et al, 1984Davis et al, , 1986Davis, Goodfellow, et al, 1987), and the details of the data acquisition can be found in those references. New data include multichannel seismic reflection profiles and heat flow determinations; the details of acquisition and processing of these data are described in Rohr et al (1992) and in this paper.…”
Section: Introductionmentioning
confidence: 99%